Mexico Through Russian Eyes, 1806-1940 - Richardson, William, 1947- (Book collections on Project MUSE., 1988)
In this book, the author analyzes the descriptions given of Mexico by an assortment of Russian visitors, from the early nineteenth through the twentieth century. He finds that Russians had a particular empathy for the Mexicans, sharing a perceived similarity in their histories: conquest by a foreign power; a long period of centralized, authoritarian rule; an attempt at liberal reform followed by revolution.